African Development Bank and Guinea-Bissau - A N Zharov; - Vieira Ivanildo (Vestnik RUDN. International Relations, 2010)
The article is focused on the analysis of African Development Bank activities in one of the poorest African countries Guinea-Bissau. Two main programs of the Bank in the country from the point of dynamics and format are considered.